A “Distributive” or a “Collective” Approach to Sentences? - Łukowski, Piotr (Logic and Logical Philosophy, 2019)
It is a well-known fact that the Russell’s antinomy arises within distributive set theory whereas it does not do so within collective set theory. n this paper, I shall propose what I shall call a “collective” understanding of a sentence as opposed to the standard, truth-functional approach which I shall term a “distributive" approach. Similar to the case with sets, the liar antinomy appears when the liar sentence is treated distributively. If, however, the sentence is understood collectively, then the liar antimony does not appear.